The lord of the rings. The fellowship of the ring [videorecording (Blu-Ray)] - Wood, Elijah, 1981-; McKellen, Ian; Tyler, Liv; Mortensen, Viggo, 1958-; Astin, Sean; Blanchett, Cate, 1969-; Rhys-Davies, John; Bloom, Orlando, 1977-; Lee, Christopher, 1922-2015; Jackson, Peter, 1961-; Tolkien, J. R. R. (John Ronald Reuel), 1892-1973 (New Line Home Entertainment, 2010)
Frodo, a meek hobbit of Middle-earth, is enlisted by the wizard Gandalf in a harrowing quest to destroy the all-powerful One Ring of the Dark Lord Sauron.